Livelihood Transitions and Determinants in Rural South Africa: Insights from a Longitudinal Analysis of Households in Bushbuckridge, Mpumalanga Province - Rusere, Farirai; Samimi, Cyrus; Mkuhlani, Siyabusa; Hunter, Lori; Twine, Wayne (Society and Natural Resources, 2025)
Rural South Africa is undergoing significant livelihood transformations, especially in areas vulnerable to socio-economic and environmental change. Using a longitudinal household panel dataset from Bushbuckridge, Mpumalanga Province, South Africa (2010–2021), this study examines livelihood dynamics, transitions, and their determinants through Hierarchical Cluster Analysis and multinomial logit regression. Three livelihood strategies were identified: (1) agrarian- local employment mix, (2) social grant-based, and (3) migrant employment-based. By 2021, around 50% of households had shifted strategies, mostly from agrarian-based to either social grant or migrant employment strategies. Reliance on social grants was higher among larger households and those with more elderly members, while households with more working-age adults favored migrant employment. These patterns reflect a decline in land-based livelihoods and a growing dependence on external income sources, reshaping rurality. The study highlights the need for place-based policies that promote local employment opportunities, support rural populations, and integrate social protection into rural development.
Keywords: Agrarian and local employment mix; livelihoods; migrant employment; rural; social grants